Machine learned-based visualization of the diversity of grapevine genomes worldwide and in Armenia using SOMmelier - Magaryan Kristina; Nikogհosyan Maria; Baloyan Anush; Gasoyan Hripsime; Hovhannisyan Emma; Galstyan Levon; Konecny Tomas; Arakelyan Arsen; Binder Hans (BIO Web of Conferences, 2023)
In the proposed study three major issues have been addressed: Firstly, the diversity of grapevine accessions worldwide and particularly in Armenia, a small country located in the largely volcanic Armenian Highlands, is incredibly rich in cultivated and especially wild grapes; secondly, the information hidden in their (whole) genomes, e.g., about the domestication history of grapevine over the last 11,000 years and phenotypic traits such as cultivar utilization and a putative resistance against powdery mildew, and, thirdly machine learning methods to extract and to visualize this information in an easy to percept way. We shortly describe the Self Origanizing Maps (SOM) portrayal method called “SOMmelier” (as the vine-genome “waiter”) and illustrate its power by applying it to whole genome data of hundreds of grapevine accessions. We also give a short outlook on possible future directions of machine learning in grapevine transcriptomics and ampelogaphy.